Ecological interactions, host plant defenses, and control strategies in managing soybean looper, Chrysodeixis includens (Lepidoptera: Noctuidae) - Debnath, Rahul; George, Justin; Gautam, Manish; Shafi, Insha; Kariyat, Rupesh; Reddy, Gadi V. P. (Frontiers in Insect Science, 2024)
Soybean looper (SBL), Chrysodeixis includens (Walker 1858) (Lepidoptera: Noctuidae), is one of the most damaging insect pests of soybean, Glycine max (L.) Merr., in the mid-south region of the United States, and causes significant economic losses to cotton, sunflower, tomato, and tobacco crops in the United States, Brazil, and Argentina. Soybean production in the southern region accounted for 15.5% of the total production in the United States, and yield losses due to invertebrate pests were 5.8%, or 1.09 million metric ton, in 2022. As insecticide resistance of SBL continues to rise, the lack of alternate control strategies is a serious concern. Numerous studies have been reported on pest status, distribution, semiochemical-based attractant blends, pesticides and resistance mechanisms, host-plant resistance mechanisms, and molecular tools for controlling this pest in soybeans and other crops. However, there is no comprehensive review that summarizes and discusses these research on SBL and soybeans. The current management strategies for SBL remain heavily reliant on chemical insecticides and transgenic crops. In contrast, integrated pest management (IPM) strategies are needed to control the pest in an effective and environmentally friendly way. This review examines and synthesizes the literature on SBL as a significant pest of soybeans and other important crops, highlighting recent progress in ecological interactions, host plant defenses, and control strategies and identifying information gaps, thereby suggesting avenues for further research on this pest.